Student Perceptions Regarding the Use of a Computer-Based Test (CBT) System at State Junior High School 3 Sungai Betung - Prima Senja Sis Ha Abadi; Indri Astuti; Eny Enawaty (Institut of Shanti Bhuana, 2024)
The use of computer-based assessment (CBT) in education is increasing, but students’ perceptions of it are still under-researched. This study aims to explore students’ perceptions of the use of CBT in SMPN 3 Sungai Betung, a junior high school in South Kalimantan. This study uses a quantitative method with a questionnaire instrument filled by 94 students. The results show that students have positive responses to CBT, in terms of trust, comfort, and academic performance. However, students also face technical constraints, such as network problems and HP operation. This study recommends improving technological literacy, additional training, and ensuring the availability of good and adequate networks for CBT optimization. This study also emphasizes the role of teachers in supporting students to overcome technical constraints, as well as attention to the aspect of justice in technology access. Thus, CBT can be an effective evaluation tool and a means of improving the quality of learning and students’ technological readiness.